Pengaruh Kejelasan Sasaran Anggaran terhadap Akuntabilitas Kinerja Instansi Pemerintahan dengan Pengawasan Internal sebagai Variabel Moderasi (Studi Kasus pada SKPD Kota Yogyakarta) - Erawati, Teguh (AKMENIKA, 2018)
Budgets are one of the most important and relevant things in local government, because budgets have an impact on performance that is attributed to the function of government as the State's hearing. Through a clear budget it will have an impact on the effectiveness of government work plans and accountability processes on a periodic basis. The purpose of this study is to determine the relationship of clarity of budget targets to the performance accountability of government agencies and internal control as a moderation variable. The population used in this study is SKPD Yogyakarta. The type of data in this study is quantitative. The data sources used are primary data sourced from the distributed kusioner. The analysis technique used is simple regression, t test, r test and pure moderation test. The results of this study is the clarity of budget targets have a positive effect on the performance accountability of government agencies and internal controls can strengthen the relationship of variable clarity of budget targets to the performance accountability of government agencies.